Learning activities using videos to strengthen intercultural competence in higher education students - Cano, John; Ricardo Barreto, Carmen; Mizuno Haydar, Jorge; Llinas Solano, Humberto (Revista Colombiana de Ciencias Sociales, 2022)
The use of properly designed educational videos has proven effective in strengthening intercultural competence in higher education. In this article, we present the results of an investigation whose objective was to determine the characteristics of learning activities that use videos to promote the development of the intercultural competence of students of virtual courses. The study was carried out using a mixed approach in which quantitative and qualitative techniques were used for data collection and analysis. The results showed that the significant changes in students occurred when the activities were based on videos that presented different situational and real contexts, promoting cultural knowledge, critical reflection and, experiential analysis. The role of the teacher is paramount in the design of activities and in their role as facilitator and guiding them.